2020
DOI: 10.2147/cmar.s265187
|View full text |Cite
|
Sign up to set email alerts
|

<p>CREB1 Suppresses Transcription of microRNA-186 to Promote Growth, Invasion and Epithelial–Mesenchymal Transition of Gastric Cancer Cells Through the KRT8/HIF-1α Axis</p>

Abstract: Background: The cAMP response element-binding protein 1 (CREB1) was initiated as a potential target for cancer treatment. This research was conducted to probe the effect of CREB1 in the progression of gastric cancer (GC) and the molecules involved. Materials and Methods: CREB1 expression in GC tissues and cell lines (AGS and MKN-45) as well as that in normal tissues and in gastric mucosa cell line (GES-1) was detected. The correlation between CREB1 expression and prognosis of GC patients was determined. Artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…CREB1 is abundantly upregulated in gastric cancer and high expression of CREB1 is associated with dismal prognosis in patients. 25 CREB1 is upregulated in bladder cancer and knockdown of CREB1 inhibits cell proliferative and invasive capacities. 26 These results substantiate our finding that CREB1 acts as a cancerpromoting gene in cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CREB1 is abundantly upregulated in gastric cancer and high expression of CREB1 is associated with dismal prognosis in patients. 25 CREB1 is upregulated in bladder cancer and knockdown of CREB1 inhibits cell proliferative and invasive capacities. 26 These results substantiate our finding that CREB1 acts as a cancerpromoting gene in cancer.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we also discovered that attenuation of CREB1 expression exerted a similar effect as miR‐450a in breast cancer cell growth and invasion. CREB1 is abundantly upregulated in gastric cancer and high expression of CREB1 is associated with dismal prognosis in patients 25 . CREB1 is upregulated in bladder cancer and knockdown of CREB1 inhibits cell proliferative and invasive capacities 26 .…”
Section: Discussionmentioning
confidence: 99%
“…But when compared with miR-mimc + oe-NC group, the apoptotic ratio of cells in miR-mimic + oe-CREB1 group was noticeably downregulated, demonstrating that the promoting effect of miR-654-3p on SNSCC cell apoptosis was reversed by CREB1. Moreover, numerous studies reported that CREB1 overexpression is associated with epithelial–mesenchymal transition (EMT) of cancer cells in a variety of cancers ( Yan et al, 2018 ; Dong et al, 2019 ; Ma et al, 2019 ; Huang et al, 2020 ). On account of previous studies, we supposed that CREB1 may affect the EMT process of SNSCC cells; therefore, we carried out Western blotting to measure the expression levels of EMT-related proteins in each transfection group ( Figure 3F ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, CCAT2 was found to modulate the EMT phenotype through cAMP-responsive element-binding protein 1 (CREB1) expression modulation [96]. CREB1 is an oncogene that was shown to promote tumor cell proliferation, EMT transition, and metastasis in gastric cancer, CRC, and prostate cancer [102,103]. CREB1 was shown to be a target of the tumor suppressor miR-493-5p.…”
Section: Cerna Activity Of Ccat2 and Mirna Spongingmentioning
confidence: 99%